2021
DOI: 10.3389/fimmu.2021.695242
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Dysregulation in COVID-19 Patients

Abstract: The COVID-19 pandemic has reached direct and indirect medical and social consequences with a subset of patients who rapidly worsen and die from severe-critical manifestations. As a result, there is still an urgent need to identify prognostic biomarkers and effective therapeutic approaches. Severe-critical manifestations of COVID-19 are caused by a dysregulated immune response. Immune checkpoint molecules such as Programmed death-1 (PD-1) and its ligand programmed death-ligand 1 (PD-L1) play an important role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 47 publications
4
61
0
Order By: Relevance
“…After mice were injected with expanded primary NK cells, preferential killing of uninfected Calu-1 cells was observed (uninfected vs. infected: 75.88% vs. 48.35%, P = 0.0248; Figure 3, E and F), suggesting that the virally infected cells can escape from the immunosurveillance mediated by NK cells. Interestingly, the ligands HLA-ABC and PDL-1 are also induced by SARS-CoV-2 infection (Figure 3A) and could potentially contribute to the immune escape mediated by SARS-CoV-2 (41).…”
Section: Resultsmentioning
confidence: 99%
“…After mice were injected with expanded primary NK cells, preferential killing of uninfected Calu-1 cells was observed (uninfected vs. infected: 75.88% vs. 48.35%, P = 0.0248; Figure 3, E and F), suggesting that the virally infected cells can escape from the immunosurveillance mediated by NK cells. Interestingly, the ligands HLA-ABC and PDL-1 are also induced by SARS-CoV-2 infection (Figure 3A) and could potentially contribute to the immune escape mediated by SARS-CoV-2 (41).…”
Section: Resultsmentioning
confidence: 99%
“…PD-L1 interacts with the programmed death receptor 1 (PD-1) on T cells and induces tolerance or/and exhaustion [ 25 ]. More recently, due to the COVID-19 pandemic, research focus on immune checkpoint molecules has increased [ 26 ]. As evident from the literature, PD-L1 dysregulation is observed in COVID-19 patients [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, due to the COVID-19 pandemic, research focus on immune checkpoint molecules has increased [ 26 ]. As evident from the literature, PD-L1 dysregulation is observed in COVID-19 patients [ 26 ]. Moreover, studies have reported the link between PD-L1-expressing basophils and the severity of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated LDH levels are associated with cell damage. In approximately 80% of patients, lymphopenia and an increased ratio of neutrophils to lymphocytes are observed [16,18,97,98]. Mahat et al in their review and meta-analysis concluded that in patients with severe COVID-19, serum levels of CRP, ESR, PCT (procalcitonin), IL-6, IL-10, IL-2R, ferritin, SAA (serum amyloid A) and NLR (neutrophil-to-lymphocyte ratio) are significantly increased compared with people with a mild COVID-19.…”
Section: Laboratory Findingsmentioning
confidence: 99%